Regulation of Remote Workers’ Rights under the Saudi Legal System: An Analytical Study - Ghaida Rashid Al-Juhani; Amal Shalabi Khadragey (International Journal of Law Research and Studies, 2026)
This study aimed to examine the legal regulation of the rights and obligations of employees in remote work contracts by identifying the concept, characteristics, and conditions of remote work contracts, as well as the legal implications related to employees’ rights and obligations. The study adopted the analytical approach through analyzing labor laws, regulations, and procedural and guidance manuals related to remote work. The study concluded that Ministerial Decision No. (120453) defines remote work as the performance of job duties outside the traditional workplace through the use of communication and information technology while maintaining the employment relationship. The study recommended that the Saudi regulator establish a more detailed and independent legal framework for remote work contracts that addresses the specific nature of this type of work.
Keywords: Remote Work; Employment Contract; Employee Rights; Employee Obligations; Saudi Labor Law; Legal Regulation